Pengembangan Aplikasi Pengolahan Data Pembukuan Spp - Bagas Riyadi; Chaisar Abi; Gema Bagustian Perdana; Jimmy Haryansyah Putra; Aries Saifudin (Journal of Research and Publication Innovation, 2023)
Data recording applications are an information technology solution that can assist organizations in collecting, managing, and manipulating data. This research aims to develop an efficient and effective data recording application for use by an organization. The software development methodology used in this study is the Agile Model. This model was chosen because it can adapt to changing user needs and desires, as well as produce high-quality products in a short amount of time. The developed application has features such as data recording, data storage, data processing, and data analysis. Additionally, the application is also equipped with data security features that can protect data stored in the application from potential threats. The application testing results show that the developed application can produce accurate and reliable data. Furthermore, application users also find it easy to use the application and manipulate the data within it. In conclusion, the data recording application developed in this research can be a solution for organizations to collect, manage, and manipulate data efficiently and effectively. The Agile Model used in the application development also proves its effectiveness in producing high-quality products in a short amount of time.